EVIDENCE-BASED NURSING FOR PREVENTION AND MANAGEMENT OF DELIRIUM IN PATIENTS UNDERGOING CARDIAC SURGERY: CASE STUDIES - Fitri, Siti Ulfah Rifa'atul; Maneewat, Khomapak; Herliani, Yusshy Kurnia; Harun, Hasniatisari (Medical-Surgical Journal of Nursing Research, 2023)
Delirium management is critical to lowering the risk for patients as well as health care providers, such as a nurse who takes complete care of the patient and plays an important role in delirium prevention from the start of post-operative care until the patient is transferred to the ward and then discharged. The purpose of this study was to examine the usefulness of instruments for screening delirium in patients undergoing cardiac surgery as well as the effectiveness of evidence-based nursing interventions for delirium prevention and management in cardiac surgery patients. This study used a case study design with five hospitalized patients who had cardiac surgery, including patients admitted 1-2 days before or within 7 days of the procedure. Based on NICE guidelines, the authors provided data collection methods for screening for delirium and intervention for delirium prevention and management in patients following cardiac surgery. According to data acquired from five responders, two patients in the high-risk age group are already in the delirium phase, while the other three patients have not shown delirium postoperatively. The most typical intervention in all cases is re-orientation and immobility (use cardiac rehabilitation), as well as basic communication. This study attempted to integrate three screening measures for delirium, then evaluated and compared the findings to see if the patient received the same or a different score on each instrument.